The Invisible Clot Maker: Eosinophilia Causing Recurrent Prosthetic Valve Thrombosis- A Case Report - Joshi, Rheecha; Bohara, Sujan; Devkota, Sachin; Chaudhary, Jay Mangal; Thapa, Esna; Shah, Manish Kumar; Gautam, Navin Chandra (Nepalese Heart Journal, 2025)
Prosthetic valve thrombosis is a devastating complication, most often related to inadequate anticoagulation. Rare etiologies such as eosinophilia, antiphospholipid syndrome, and myeloproliferative disorders should be considered in recurrent or refractory cases. We report a 17-year-old male with a mechanical mitral valve who developed three episodes of prosthetic valve thrombosis over 9 years, the last two despite therapeutic anticoagulation. Evaluation revealed persistent eosinophilia, and tropical hypereosinophilia was diagnosed. Targeted anti-helminthic therapy resolved eosinophilia and prevented recurrence over 18 months. Beyond their role in allergic and inflammatory conditions, eosinophils release cytotoxic granule proteins, which can directly damage endothelial surfaces and disrupt the integrity of prosthetic material, facilitating platelet adhesion and aggregation. Eosinophil-derived tissue factor and inflammatory mediators further enhance local thrombogenicity. Clinically, eosinophil- driven prosthetic valve thrombosis manifests as recurrent events despite adequate anticoagulation, underscoring an immunothrombotic mechanism distinct from conventional pathways. Optimal management requires not only anticoagulation but also treatment of the underlying eosinophilic disorder to prevent recurrence.